Phonetics interference between Arabic and French in third year of Algerian primary education. - Maazouzen, Samir (Milev Journal of Research and Studies, 2018)
This study seeks to reveal the manifestations of phonetics interference in Arabic and French in an attempt from a learner to learn his second language. Language learner are often incorporating into the second language first language phonetic and could replace the ones he can’t pronounce (in the second language) by others in his own language, or from near phonemes. To reach our goal we will depend on the method of errors analysis to analyze the code language, passing through three stages: identifying the error, describing it and finally interpreting it. So we will try to understand what phonetics interference is, its causes and consequences and clarify its manifestations in pronunciation and writing letters